Diversity of pests and natural enemies in rice field agroecosystem with ecological engineering and without ecological engineering. Issue 1 (April 2020) - Ibrahim, E; Mugiasih, A
Abstract: Biodiversity is one measure of ecosystem balance, so that biodiversity is important to know the condition of the ecosystem in the fields. A high diversity index shows the high stability of the ecosystem because the food webs formed are more complex. The purpose of this study was to obtain information about the diversity of insects in the paddy ecosystem with ecological engineering and without ecological engineering. This research was conducted at the Experimental field of Tungro Disease Research Station, Lanrang Sidrap, South Sulawesi, Indonesia from June to August 2017 using the observation method by periodically observing each week starting at plants 2 weeks after planting. The design used a split-plot design consisting of 2 main plots, namely 1) Ecological Engineering Agroecosystem, using flowering plants (refugia) and pest control with andrometa which is a mixture of entomopathogenic fungus Metharizium anisopliae and bitter extract; 2) Conventional agroecosystems, without flowering plants and pest control using pesticides. The results show that the number of pests and natural enemies found in ecological engineering agroecosystem plots is higher than conventional plots. While the index value of pest diversity and natural enemies in both observation plots is classified as moderate. Therefore, the ecological engineering agroecosystem by planting refugia plants is needed to increase the number and types of arthropods of natural enemies.